Applicability of Article 53 of Law No. 22 of 2001 in Supporting the Effectiveness of the Law Against the Hoarding of Subsidized Fuel - Roziah Siti Fatima Yusuf (Universitas Negeri Gorontalo, 2023)
This study aims to analyze the applicability of Article 53 Law No. 22 of 2001 in Supporting the Effectiveness of the Law Against the Hoarding of Subsidized Fuel (from now on referred to as BBM) in the Resort Police Region of Gorontalo City and the factors that influence this. This type of empirical or field research uses a case approach and a statutory approach. The results of this study indicate the expected effectiveness of the law because, in terms of implementing the article, it is still challenging to implement and also because the lack of tightness in the distribution of subsidized fuel from Pertamina makes the hoarding easier. What influences the effectiveness of this law are factors such as the community, law enforcement, and sanctions, which still need to be stronger..